Social Capital and Health: Analyzing the Social Network of Chronically Ill People with Diabetes Type 2 in Bulgaria - Todorova, Elka (Research Papers, 2016)
This paper describes the development of ideas and issues attached to the construct of social capital. Special interest is given to the types of social capital and their effects on health. Qualitative analysis of biographical interviews of chronic illness patients with diabetes type 2 is done, the focus being to describe how different types of social capital, namely bonding, bridging and linking are used in networking in urban and rural areas. The proposed social capital support system’s interpretation is based on matching well-being, life satisfaction and happiness assessment of patients with diabetes type 2 and social capital components.